A Modified Surgical Ventricular Reconstruction in Post-infarction Mice Persistently Alleviates Heart Failure and Improves Cardiac Regeneration - Ma, Siyuan; Yan, Junyu; Yang, Dexuan; Liao, Wangjun; Bin, Jianping; Lin, Hairuo; Liao, Yulin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Large ventricular aneurysm secondary to myocardial infarction (MI) results in severe heart failure (HF) and limits the effectiveness of regeneration therapy, which can be improved by surgical ventricular reconstruction (SVR). However, the conventional SVR procedures do not yield optimal long-term outcome in post-MI rodents. We hypothesized that a modified SVR procedure without aggressive purse string suture would persistently alleviate HF and improve cardiac regeneration in post-MI mice. Methods: Adult male C57 mice were subjected to MI or sham surgery. Four weeks later, mice with MI underwent SVR or 2nd open-chest operation alone. SVR was performed by plicating the aneurysm with a single diagonal linear suture from the upper left ventricle (LV) to the right side of the apex. Cardiac remodeling, heart function and myocardial regeneration were evaluated. Results: Three weeks after SVR, the scar area, LV volume, and heart weight/body weight ratio were significantly smaller, while LV ejection fraction, the maximum rising and descending rates of LV pressure, LV contractility and global myocardial strain were significantly higher in SVR group than in SVR-control group. The inhibitory effects of SVR on LV remodeling and HF persisted for at least eight-week. SVR group exhibited improved cardiac regeneration, as reflected by more Ki67-, Aurora B- and PH3-positive cardiomyocytes and a higher vessel density around the plication area of the infarcted LV. Conclusions: SVR with a single linear suture results in a significant and sustained reduction in LV volume and improvement in both LV systolic and diastolic function as well as cardiac regeneration.